PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK,TALK WRITE UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR PESERTA DIDIK (Studi Tindakan Kelas pada Mata Pelajaran Bahasa Inggris Kelas X SMA Negeri 1 Merapi Selatan Kabupaten Lahat) - Winarto Winarto (DIADIK, 2020)
The research purpose is to describe the cooperative type learning model Think,Talk,Write to increase   the students’ independence   and achievement of the student learning at English subject of the first class SMA  Negeri  1  Merapi  Selatan  Lahar  Regency.  The  subjects  of  the research  are  the  students  of  X  IPA  at  the  second  semester  of  the academic year 2019/2020 SMA Negeri 1 Merapi Selatan. The research design used is   classroom action research and quotient experiment. The instuments used are the tes instruments of objective questions given ti the students at every cycle.Non test instruments used are the observation sheet of teacher’s activity and the observation sheet of students’ independence. The data of test result is analized by using descriptive statistics and the data of on test result is analized by using quantitative description. From the  result of this research  shows that the cooperative type learning model Think,Talk and Write  can increase independece and achievement of the students learning of X IPA class SMA Negeri 1 Merapi Selatan Lahat regency.